Removal of methylene blue and tetracycline from water using peanut shell derived adsorbent prepared by sulfuric acid reflux. Issue 1 (February 2019) - Islam, Md. Tariqul; Hyder, AHM Golam; Saenz-Arana, Ricardo; Hernandez, Cesar; Guinto, Thomas; Ahsan, Md Ariful; Alvarado-Tenorio, Bonifacio; Noveron, Juan C.
Graphical abstract: Modification of peanut-shell into a high-capacity adsorbent using the sulfuric acid reflux technique for the removal of methylene blue and tetracycline from water. Highlights: Sulfonated peanut shell (PNS-SO3 H) was prepared by sulfuric acid reflux. PNS-SO3 H adsorbed methylene blue (MB) up to 1250 mg/g. PNS-SO3 H adsorbed tetracycline (TC) up to 303 mg/g. PNS-SO3 H can adsorb MB and TC from tap water. Column packed with PNS-SO3 H can continuously filter MB from tap water. Abstract: Preparation of economically and environmentally viable adsorbents out of biomass has achieved immense interest for the water treatment purposes. This study reported the synthesis of a low-cost and high-capacity adsorbent viz. sulfonated peanut shells (PNS-SO3 H) by a facile sulfuric acid (H2 SO4 ) reflux technique. The concentrated H2 SO4 reflux resulted in the carbonization and sulfonation of the peanut shell. Organic pollutants e.g. methylene blue (MB) and tetracycline (TC) were removed from water by the PNS-SO3 H. The adsorption characteristics were evaluated as the function of pH, time, initial adsorbate concentration, and temperature in batch adsorption tests. At basic pH, MB showed an increasing trend of adsorption capacity, whereas TC demonstrated the opposite trend. The maximum adsorption capacity was found to be 1250 and 303 mg/g for MB and TC, respectively. In comparison to the pristine peanut shell, the PNS-SO3H demonstrated about 100 and 40 times higher adsorption capacity for MB and TC, respectively. The batch adsorption results were in good fit with the Langmuir isotherm model and the adsorption kinetics followed pseudo-second-order kinetics. The adsorption of MB and TC was found to be endothermic and thereby an increased adsorption capacity was obtained at elevated temperature. The adsorption performance of MB and TC from tap water was also studied and similar adsorption behavior as deionized water was obtained. A packed column was prepared with PNS-SO3 H for the filtration of 20 ppm MB solution from tap water. The column was able to filter 36 liters of MB solution with 100% removal efficiency.